Determinants Present in the Receptor Carboxy Tail Are Responsible for Differences in Subtype-Specific Coupling of β-Adrenergic Receptors to Phosphoinositide 3-Kinase. (13th January 2009) - Simard, Julie; Boucher, Matthieu; Massé, Rachel; Hébert, Terence E.; Rousseau, Guy
Abstract : An agonist-occupiedβ 2 -adrenergic receptor (β 2 -AR) recruits G protein receptor kinase-2 (GRK2) which is recruited to the membrane. Thus, the physical proximity of activatedβ 2 -AR and PI-3K allows the activation of the latter. In contrast, it has been observed that theβ 1 -AR is unable to activate the PI-3K/Akt pathway. We hypothesized that the difference might be due to molecular determinants present in the carboxy termini of the twoβ -AR subtypes. Using transiently transfected HEK 293 cells expressing eitherβ 1 - orβ 2 -AR, we also observed that in presence of an agonist, β 2 -AR, but notβ 1 -AR, is able to activate the PI-3K/Akt pathway. Switching the seventh transmembrane domain and the carboxy tail between the two receptors reverses this phenotype; that is, β 1 × β 2 -AR can activate the PI-3K/Akt pathway whereasβ 2 × β 1 -AR cannot. Pretreatment with pertussis toxin abolished the activation of PI-3K byβ 2 - orβ 1 × β 2 -AR stimulation. Ligand-mediated internalization of theβ 2 -AR induced by a 15-minute stimulation with agonist was abolished in the presence of a dominant negative of PI-3K or following pertussis toxin pretreatment. These results indicate that the subtype-specific differences in the coupling to PI-3K/Akt pathway are due to molecular determinants present in the carboxy tail of the receptor and further thatβ 2 -AR activates PI-3K via a pertussis toxin-sensitive mechanism.